The effect of transformational leadership, teachers' openness to experience and gender on innovative work behavior in higher education institutions - Habtu Gebreslassie Bahru; Amare Sahle Abebe; Tilaye Kassahun Ayen (College of education, Bahir Dar University, 2023)
This study examined the effect of transformational leadership, openness to experience and gender on innovative work behavior in higher education institutions found in Amahara National Regional State. Among ten public universities, Bahir Dar, Gondar, Wollo, Debre Tabor and Debark were selected using a lottery sampling technique. Using G*power, from 1,726 teachers, 550 of them were selected as sample of the study. Data was collected through questionnaire and analyzed by structural equation modeling and Hayes PROCESS Macro. The results reveled that the positive influence of transformational leadership on innovative work behavior is mediated by openness to experience. The results also depicted that gender did not moderate the indirect effect of transformational leadership on innovative work behavior. Therefore, it can be concluded that the indirect effect of deans' transformational leadership on teachers' innovative work behavior is not conditional as a function of gender. This finding provides an empirically supported knowledge to explain how transformational leadership influences innovative work behavior in higher education contexts.